Conjunctival leiomyosarcoma: A fairly common tumour in an uncommon site. (7th August 2017) - Wadee, Reubina
Background: Leiomyosarcomas of soft tissue are malignant tumours that are not infrequently encountered in clinical medicine and histopathology. Such sarcomas of the eye are, however, a rare occurrence. Purpose: Herein, the histopathological features of a case of conjunctival leiomyosarcoma are described. A 38-year-old HIV-positive male, who was otherwise fit and healthy, presented with redness of his right eye and a mass of the conjunctiva. Clinically, he did not have any soft-tissue masses elsewhere in the body. Method: He underwent monoblock excision of the conjunctival mass which was confirmed histologically to be a leiomyosarcoma. Unfortunately, the patient had not returned for follow-up examination. Conclusion: The differential diagnosis of a conjunctival spindle cell neoplasm is broad. While a spindle cell carcinoma is the most likely tumour, other tumours must be borne in mind so as not to misdiagnose primary sarcomas in this unusual location.